Civil society and social movements in an ethnically divided society: the case of Malaysia, 1981-2001 - Brown, Graham K. (2004)
This thesis examines the relationship between civil society, social movements and the state in ethnically-divided countries, using the case study of Malaysia. The argument begins with the observation that the respective literatures on civil society and social movements occupy a broadly congruent paradigm, but the relationship between the two is poorly theorised. Through a critical discussion of existing approaches, a synthesis of civil society and social movements theory is produced, which argues for a dualistic interpretation that emphasises both institutional linkages and cultural and discursive relationships. It is further argued that this latter aspect is of particular importance in ethnically-divided countries, as cultural differences between groups may hamper the effective mobilisation of movements. Thus may exist a form of ‘slippage’ between civil society and movement mobilisation, unidentified in much of the literature that tends to view the two as dynamically homogenous.